Effect And Predictive Value Of Routine Preoperative Laboratory Testing For Endoscopic Retrograde Cholangiopancreatography. (June 2020) - Jokelainen, J.; Ismail, S.; Kylänpää, L.; Udd, M.; Mustonen, H.; Lindström, O.; Pöyhiä, R.
Background and Aims: Several studies and guidelines are questioning routine preoperative laboratory tests in surgical and endoscopic procedures. Their effect in endoscopic retrograde cholangiopancreatography is not currently known. This study was carried out to evaluate the risk of adverse effects in endoscopic retrograde cholangiopancreatography and their association with preoperative lab tests. Materials and Methods: A single-center, prospective observational study on all 956 patients undergoing 1196 endoscopic retrograde cholangiopancreatographies in the Endoscopy Unit of Helsinki University Central Hospital from 1 March 2012 to 28 February 2013. Routine preoperative laboratory test results (basic blood count, creatinine, potassium, sodium, international normalized ratio/thromboplastin time, and amylase), health status, medication, and demographic information of all patients were analyzed in relation to adverse effects related to endoscopic retrograde cholangiopancreatography and procedural sedation. Results: Multivariate analysis showed post–endoscopic retrograde cholangiopancreatography pancreatitis (43 cases, 3.6%) to have no association with abnormal routine preoperative laboratory tests. Respiratory depression caused by sedation (128 cases, 11%) was not associated with abnormal routine preoperative laboratory tests, and anemia was found to be a slightly protecting factor. Cardiovascular depression caused by sedation was associated with thrombocytopenia (odds ratio = 1.87, p = 0.025) and, in male patients, hyponatremia (odds ratio = 3.66, p < 0.001). Incidence of other adverse effects was too low for statistical analysis. Conclusion: Routine universal preoperative lab testing was not found to be successful in predicting adverse effects in endoscopic retrograde cholangiopancreatography procedures. Laboratory testing should be done focusing on each patient's individual needs.